PERSPECTIVES OF E-CONTENT: A SYSTEMATIC REVIEW - Dr.iInderpreet Kaur, Ms Jyoti ,Ms.Raskirat (International Journal of Advanced Science and Technology, 2020)
Throughout recent decades, as the issue of social advancement has gone to the fore, the drive to improve access to instruction has been behind the development in into e-learning. Technology is the use of scientific knowledge for the welfare of all. Technology has become an integral part of life these days. Technology has also changed the process of teaching and learning. E-content is the outcome of usage of technology in our classrooms. E-content do not tend to replace traditional teaching and learning but are expected to complement each other. So before proceeding to the development of E-content, it is necessary to review, all the perspectives of e-content. The current systematic review has brought up the issue of the presence of studies tending to the particular needs of people. In reality, e-learning is required to be one of the basic tools for improving access to instruction and at last supporting social incorporation. The systematic literature review was performed through a four-step process including an exhaustive search of scientific literature databases, the selection of studies through exclusion and inclusion criteria, and literature analysis and synthesis. The main results are 38% studies regarding the development of econtent, 28% studies has analyzed impact of e-learning, and 19% studies carried out on the challenges in the development and implementation of e-content. Finding the gaps of the examinations, no paper has estimated cognitive load after the usage of e-content, alongside this none of the investigations estimated how the reasoning abilities change after the execution of e-content, Which turns out as the hole of the research?